2020
DOI: 10.1007/s11010-020-03726-6
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine had neuroprotective effects on hippocampal neuronal cells via targeting lncRNA SHNG16 mediated microRNA-10b-5p/BDNF axis

Abstract: Dexmedetomidine (DEX), a highly selective alpha2 adrenergic receptor agonist, is a commonly used anesthetic drug in surgical procedures. Previous studies have indicated that DEX exerts neuroprotective effects while the detailed mechanism has not been fully elucidated. Here, we aim to study the role of lncRNA SHNG16 in DEX-induced brain protection and its underlying molecular mechanism. The rats underwent middle cerebral artery occlusion (MCAO) surgery and oxygen-glucose deprivation (OGD)-treated HT22 hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…With rising concern about ICU delirium and neurotoxicity effects of various sedatives on the developing brain, dexmedetomidine has become the preferred choice of sedative in the ICU, given its reported neuroprotective effect (15)(16)(17)(18)(19)(20)(21)(22). This is in contrast to procedural sedation where the use of dexmedetomidine is not routine.…”
Section: Discussionmentioning
confidence: 99%
“…With rising concern about ICU delirium and neurotoxicity effects of various sedatives on the developing brain, dexmedetomidine has become the preferred choice of sedative in the ICU, given its reported neuroprotective effect (15)(16)(17)(18)(19)(20)(21)(22). This is in contrast to procedural sedation where the use of dexmedetomidine is not routine.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence illustrates that Dex possesses neuroprotective effects in nervous system diseases [11][12][13]. Herein, we further explored the effects of Dex on IS-induced neuronal damage in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It would therefore appear that under certain experimental conditions DEX may induce neurotoxicity in brain slices and these subsequent effects may involve a variety of signalling pathways. However, in many other instances, DEX appears not only to be non-neurotoxic but also neuroprotective against the toxicity induced by other anesthetic agents such as sevoflurane, propofol or ketamine 22,64,65 . Previous studies have shown a number of anesthetic agents affect synaptic structures and function 33,66,67 ; however, similar conclusive evidence for DEX is missing.…”
Section: Discussionmentioning
confidence: 99%